Hubungan Pola Menyusui dan Usia Penyapihan dengan Status Gizi Anak Baduta (6-24 Bulan) di Kota Kendari Tahun 2014 - M.E, Putu Eka Eka (Sekolah Tinggi Ilmu Kesehatan Karya Kesehatan, 2014)
The growth and development of infants is largely determined by the amount of breast milk obtained, including energy and other nutrients contained in the breast milk. If the mother's health after giving birth is good, breastfeeding is the most ideal way of feeding for the first 4-6 months from birth, because breast milk can meet the nutritional needs of the baby. After breast milk no longer contains enough protein and calories, a baby begins to need complementary drinks/foods. This study aims to determine the relationship between breastfeeding patterns and weaning age with the nutritional status of children under two years old (6-24 months) in Kendari City in 2014. This research is an analytical descriptive with a cross sectional study design and has been carried out from 21 to 28 February 2014 in Kendari City. The population in this study were all mothers who had children under the age of 6-24 months in Kendari City, namely 415 people and a sample of 52 people who were taken by purposive sampling, the data was obtained using a questionnaire and tested using the Chi-Square test. The results of the study were obtained from 33 Baduta whose nutritional status was lacking, most of which were 77.8% of their breastfeeding patterns in the category and from 19 Badutas whose nutritional status was adequate, most of them, namely 68.7% of their breastfeeding patterns, were in the poor category. malnutrition, mostly 76.8% of the weaning age was in the inappropriate category and of the 33 Baduta whose nutritional status was lacking, most of the 76.8% of the weaning age were in the inappropriate category. The conclusion in this study is the relationship between breastfeeding patterns and weaning age with the nutritional status of children under two years old (6-24 months) in Kendari City in 2014, with p = 0.001 for breastfeeding patterns and p = 0.015 for weaning age. Suggestions in this study are for the Kendari City Health Office to be able to determine policies in an effort to overcome the problem of undernutrition status and appropriate weaning efforts. For mothers of toddlers to increase weaning of babies at the age of 6 months. For further researchers, in order to be able to examine the factors causing the inappropriate age of weaning carried out by mothers under two years old and the causes of low nutritional status under two years